THE USE OF gusA REPORTER GENE TO MONITOR THE SURVIVAL OF INTRODUCED BACTERIA IN THE SOIL - Husen, Edi (Indonesian Journal of Agricultural Science, 2005)
An effective marker to monitor the survival of introduced bacteria in the soil is required for further evaluation of their beneficial effects on plant growth. This study tested the use of gusA gene as a marker to trace the fate of three Gram negative bacteria in the root, rhizosphere, and soil. The study was conducted at the laboratory and greenhouse of the National Institute of Molecular Biology and Biotechnology, Philippines from January to December 2001. Isolates TCaR 61 and TCeRe 60, and Azotobacter vinelandii Mac 259 were selected as test bacteria based on their ability to produce indole-3acetic acid and solubilize precipitated phosphate, which may promote plant growth in the field. These bacteria were marked with gusA reporter gene from Escherichia coli strain S17-1(Î»-pir) containing mTn5SSgusA21. The gusA (Î²-glucuronidase) gene from the donor (E. coli) was transferred to each bacterium (recipient) through bacterial conjugation in mating procedures using tryptone-yeast agar followed by the selection of the transconjugants (bacteria receiving gusA) in tryptone-yeast agar supplemented with double antibiotics and X-GlcA (5bromo-4chloro- 3indoxyl-Î²-D-glucuronic acid). The antibiotics used were rifampicin and either streptomycin or spectinomycin based on antibiotic profiles of thedonor and recipients. The results showed that the insertion of gusA gene into bacterial genomes of the recipient did not impair its phenotypic traits; the growth rates of the transconjugants as well as their ability to produce indole-3acetic acid and solubilize precipitated phosphate in pure culture were similar to their wild types. All transconjugants colonized the roots of hot pepper (Capsicum annuum L.) and survived in the rhizosphere and soil until the late of vegetative growth stage. The distinct blue stainingof transconjugants as the expression of gusA gene in media containing X-GlcA coupled with their resistance to rifampicin and streptomycin or spectinomycin made them easier to be recognized and evaluated.